EXPERIMENTAL PRODUCTION OF ORGANIC FERTILIZER THROUGH SOLID DOMESTIC AND MARKET BIORERESIDUES TO IMPROVE SOLANUM TUBEROSUM L. BIOMASS - Florez Ponce de León, Walter (2019)
The search for natural sources to produce organic fertilizer, even when they are waste products, constitutes a sustainable environmental solution as well as efficient for the organoleptic quality in crops yield. The aim of this study was to experimentally produce organic fertilizer by means of household and market solid biowaste to improve the biomass of Solanum tuberosum L. Residues of purple corn, barley, eggshells, bananas, potatoes and avocado seeds were collected from January to December 2017. Th e residues were dried at room temperature (72-96 h) and then ground for mixing until pulverization of fl our was obtained. Th e characterization was based on 100 g: 25% of purple corn, 25% of barley, 5% of eggshell, 20% of banana peel, 10% of potato skin and 15% of seed of avocado. The multi-component mixture was used as an organic fertilizer applying to S. tuberosum cultured soils. When comparing two groups of treatments withoutorganic fertilizer and with organic fertilizer, the results indicated that there were statistically signifi cant diff erences (p <0.05) in the biomass (g) (269.012 ± 1.70 and 274.88 ± 0.76). It was concluded that, under experimental conditions, a significant biomass of S. tuberosum was obtained from the composition and mixture of bio-waste that was used for the preparation and application of organic fertilizer.